Penerapan Teknik Make a Match Terhadap Kemampuan Membaca Anak SD Kelas II di SDN 108028 Serdang Bedagai - Dinda Yarshal; Dewi Fitria (Universitas Islam Sumatera Utara, 2021)
The purpose of this study was to find out how the application of the make a match technique to the reading skills of second grade elementary school children at SDN 108028. This study used a descriptive qualitative research type with the research subject of teachers and students. Data collection techniques using interviews, observation, and documentation. Based on the results of the analysis and discussion, the writer concludes regarding the application of the make a match technique to the reading ability of grade II children that the teacher has not fully realized the stages of the make e match technique perfectly in accordance with the theory. The realization seen in the application, from the nine steps of the game, the teacher was only able to carry out six steps. This is due to the lack of time management carried out by the teacher. Supposedly for maximum results the teacher must apply the steps of the make a match technique in accordance with the existing theory in developing the reading ability of Grade II elementary school children in SDN 108028.